Climatologia da temperatura da alta troposfera e baixa estratosfera na região sul da América do Sul - Reis, Marco Antônio Godinho dos (2024)
The region known as the Upper Troposphere and Lower Stratosphere (UTLS) plays a key role in the behavior and understanding of radiative, dynamic, chemical, and microphysical processes in the troposphere and stratosphere. This work aimed to investigate the temperature climatology in the UTLS region from 1983 to 2022 over the central region of Rio Grande do Sul state. Using 40 years of vertical temperature profile data from the ERA-5 reanalysis by the European Centre for Medium-Range Weather Forecasts (ECMWF), time series at five different UTLS vertical levels were compiled and evaluated for quality through intercomparison with operational radiosonde data from the Santa Maria Air Base and meteorological campaigns. The time series were analyzed for major interannual, seasonal, and subsazonal variability modes through wavelet analysis and Morlet wavelet transformation. Additionally, potential trend signals in the temperature time series were investigated using the Mann-Kendall (MK) statistical test. The temperature profile quality assessment for the study region showed good agreement between observational radiosonde data and ERA-5 reanalysis, with relative profile differences less than 5% of absolute temperature values. Monthly climatology analysis indicated a general dominance of the annual oscillation across the five isobaric levels, with an additional influence of the semi-annual cycle at the 150 and 30 hPa levels. The Mann-Kendall test consistently pointed to warming in the upper troposphere levels and cooling in the lower stratosphere. Finally, the wavelet analysis revealed a predominance of subsazonal and seasonal periodicities over the 40 years, suggesting possible oscillations and associated phenomena.